Association between therapeutic alliance, care satisfaction, and pharmacological adherence in bipolar disorder. - Sylvia, L; Hay, A; Ostacher, M; Miklowitz, D; Nierenberg, A; Thase, M; Sachs, G; Deckersbach, T; Perlis, R (2013)
OBJECTIVES: We sought to understand the association of specific aspects of care satisfaction, such as patients' perceived relationship with their psychiatrist and access to their psychiatrist and staff, and therapeutic alliance with participants' likelihood to adhere to their medication regimens among patients with bipolar disorder. METHODS: We examined data from the multicenter Systematic Treatment Enhancement Program for Bipolar Disorder, an effectiveness study investigating the course and treatment of bipolar disorder. We expected that participants (n = 3037) with positive perceptions of their relationship with their psychiatrist and quality of psychopharmacologic care, as assessed by the Helping Alliance Questionnaire and Care Satisfaction Questionnaire, would be associated with better medication adherence. We utilized logistic regression models controlling for already established factors associated with poor adherence. RESULTS: Patients' perceptions of collaboration, empathy, and accessibility were significantly associated with adherence to treatment in individuals with bipolar disorder completing at least 1 assessment. Patients' perceptions of their psychiatrists' experience, as well as of their degree of discussing medication risks and benefits, were not associated with medication adherence. CONCLUSIONS: Patients' perceived therapeutic alliance and treatment environment impact their adherence to pharmacotherapy recommendations. This study may enable psychopharmacologists' practices to be structured to maximize features associated with greater medication adherence.